The Influence of Perceived Organizational Support on Police Job Burnout: A Moderated Mediation Model - Zeng, Xiaoqing; Zhang, Xinxin; Chen, Meirong; Liu, Jianping; Wu, Chunmiao (Frontiers in Psychology, 2020)
Objective Based on the theory of perceived organizational support (POS), conservation of resource (COR) and job demands-resources (JD-R) model, this study establishes a moderated mediation model to test the role of job satisfaction in mediating the relationship between POS and job burnout, as well as the role of regulatory emotional self-efficacy (RES) in moderating the above mediating process. Methods A total of 784 police officers were surveyed with the POS Scale, the Job Burnout Questionnaire, the RES Scale, and the Minnesota Job Satisfaction Questionnaire. Results (1) After controlling for gender, seniority, age, police classification, education, and marital status, regression analysis showed a significant negative correlation between POS and burnout (r = −0.42, p < 0.01), and the former had a significant negative predictive effect on job burnout (β = −0.42, p < 0.001). (2) The mediating effect test shows that job satisfaction plays a partial role in mediating the relationship between POS and job burnout. (3) Through the analysis of the moderated mediation model test, RES moderates the first half of the path of “POS → job satisfaction → job burnout.” Conclusion POS not only directly affects police job burnout but also indirectly affects police job burnout through job satisfaction. RES enhances the influence of organizational support on job satisfaction. This study indicates the combined effect of POS, job satisfaction, and RES on job burnout and has certain guiding significance for alleviating police job burnout.